REPRESENTATION OF GROUPS BY HOMOMORPHISM - Bedaiwi, S. (Iraqi Journal of Science, 2024)
Issacs [1] shows that if*  :GF is a homomorphism (* F is the multiplicativegroup of the field F) and G is a group, then one can define (g)  ((g)) which isan F-representation of G of degree 1 affords  as character. [2,3,4] inspires us to dothe following: given a homomorphism* f :GG then we define a representation ofG by the homomorphism f from a given F-representation* *  :G GL(n,F)of* G as*    f . We study this kind of representations and their associatedcharacters.